4-D flow magnetic resonance imaging: blood flow quantification compared to 2-D phase-contrast magnetic resonance imaging and Doppler echocardiography. - Gabbour, Maya; Schnell, Susanne; Jarvis, Kelly; Robinson, Joshua D; Markl, Michael; Rigsby, Cynthia K (Pediatric Radiology, 2015)
Background: Doppler echocardiography (echo) is the reference standard for blood flow velocity analysis, and two-dimensional (2-D) phase-contrast magnetic resonance imaging (MRI) is considered the reference standard for quantitative blood flow assessment. However, both clinical standard-of-care techniques are limited by 2-D acquisitions and single-direction velocity encoding and may make them inadequate to assess the complex three-dimensional hemodynamics seen in congenital heart disease. Four-dimensional flow MRI (4-D flow) enables qualitative and quantitative analysis of complex blood flow in the heart and great arteries.Objectives: The objectives of this study are to compare 4-D flow with 2-D phase-contrast MRI for quantification of aortic and pulmonary flow and to evaluate the advantage of 4-D flow-based volumetric flow analysis compared to 2-D phase-contrast MRI and echo for peak velocity assessment in children and young adults.Materials and Methods: Two-dimensional phase-contrast MRI of the aortic root, main pulmonary artery (MPA), and right and left pulmonary arteries (RPA, LPA) and 4-D flow with volumetric coverage of the aorta and pulmonary arteries were performed in 50 patients (mean age: 13.1 ± 6.4 years). Four-dimensional flow analyses included calculation of net flow and regurgitant fraction with 4-D flow analysis planes similarly positioned to 2-D planes. In addition, 4-D flow volumetric assessment of aortic root/ascending aorta and MPA peak velocities was performed and compared to 2-D phase-contrast MRI and echo.Results: Excellent correlation and agreement were found between 2-D phase-contrast MRI and 4-D flow for net flow (r = 0.97, P < 0.001) and excellent correlation with good agreement was found for regurgitant fraction (r = 0.88, P < 0.001) in all vessels. Two-dimensional phase-contrast MRI significantly underestimated aortic (P = 0.032) and MPA (P < 0.001) peak velocities compared to echo, while volumetric 4-D flow analysis resulted in higher (aortic: P = 0.001) or similar (MPA: P = 0.98) peak velocities relative to echo.Conclusion: Excellent flow parameter agreement between 2-D phase-contrast MRI and 4-D flow and the improved volumetric 4-D flow velocity analysis relative to echo suggests that 4-D flow has the potential to become a clinical alternative to 2-D phase-contrast MRI.